High Treason - Mills, DiAnn (Carol Stream, Illinois Tyndale House Publishers, Inc., 2018)
When Saudi Prince Omar bin Talal visits Houston to seek cancer treatment for his mother, an attempt on his life puts all agencies on high alert. Special Agent Kord Davidson is the lead on the prince's protective detail because of their long-standing friendship, but he's surprised--and none too happy--when the CIA brings one of their operatives, Monica Alden, in on the task force after the assassination attempt.
Keywords: Government investigators -- Fiction; Attempted assassination -- Fiction; Romantic suspense fiction; Christian fiction; Romance fiction